2014
DOI: 10.1103/physrevd.89.044005
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and entropy spectrum of the BTZ black hole with torsion

Abstract: In this paper, we study the phase transition and the entropy spectrum of BTZ black hole obtained in a model of three-dimensional gravity with torsion. By calculating the heat capacity we find that the BTZ black hole we considered will experience phase transition at some critical point. This indicates that the critical behaviors of black holes do not only depend on the spacetime metric, but have to do with the theory of gravity under consideration. In addition we derived the entropy spectrum of the BTZ black ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…It was soon realized that the critical exponents of the 4-dimensional Reissner-Nordström AdS black hole are the same as those in the van der Waals liquid-gas phase transition [12], completing an analogy explored previously in a more restricted context [20][21][22][23]. Subsequently a broad range of new thermodynamic behaviour was discovered, including reentrant phase transitions, tricritical points, and more general van der Waals behaviour with standard critical exponents [13,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], with an extensive review of these issues in the context of rotating black holes presented in [43].One of the most recent discoveries of interest was obtained in 3rd-order Lovelock gravity [28,44]. Multiplereentrant-phase-transition behaviour as well an isolated critical point with non-standard critical exponents for a D = 7 third-order (cubic) Lovelock asymptotically AdS black hole were found.…”
mentioning
confidence: 85%
“…It was soon realized that the critical exponents of the 4-dimensional Reissner-Nordström AdS black hole are the same as those in the van der Waals liquid-gas phase transition [12], completing an analogy explored previously in a more restricted context [20][21][22][23]. Subsequently a broad range of new thermodynamic behaviour was discovered, including reentrant phase transitions, tricritical points, and more general van der Waals behaviour with standard critical exponents [13,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], with an extensive review of these issues in the context of rotating black holes presented in [43].One of the most recent discoveries of interest was obtained in 3rd-order Lovelock gravity [28,44]. Multiplereentrant-phase-transition behaviour as well an isolated critical point with non-standard critical exponents for a D = 7 third-order (cubic) Lovelock asymptotically AdS black hole were found.…”
mentioning
confidence: 85%
“…From this perspective one can show that the celebrated Hawking-Page phase transition [19] can be understood as being analogous to a solid/liquid phase transition [1], and more generally that the 4-dimensional Reissner-Nordström AdS black hole can be interpreted as a Van der Waals fluid with the same critical exponents [13]. Along with more general Van der Waals behaviour with standard critical exponents [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], other 'chemical' black hole behaviour was subsequently discovered, such as reentrant phase transitions [37], tricritical points [38], Carnot cycles [39], isolated critical points [40,41], extensions to black rings [42], and superfluidity [43].…”
Section: Introductionmentioning
confidence: 97%
“…Black holes, being characterized by only three parameters, are the most simplest thermodynamic system. In particular, it has been found that AdS black holes have fruitful phase structures [5][6][7][8][9][10][11][12][13][14][15][16][17]. Therefore, in this paper we choose the charged AdS black hole to make the first attempt.…”
Section: Introductionmentioning
confidence: 99%